An Open-Label 52-Week Clinical Extension Comparing Duloxetine with Routine Care in Patients with Diabetic Peripheral Neuropathic Pain - Wernicke, Joachim F.; Wang, Fujun; Pritchett, Yili L.; Smith, Timothy R.; Raskin, Joel; D'Souza, Deborah N.; Iyengar, Smriti; Chappell, Amy S. (Pain medicine (Malden, Mass.), 2007)
ABSTRACT Objective.  To assess the safety of duloxetine at a fixed‐dose of 60 mg twice daily (BID) for up to 52 weeks, and compare duloxetine with routine care in the management of patients with diabetic peripheral neuropathic pain (DPNP). Design and Interventions.  Patients who completed a 13‐week, randomized, double‐blind, placebo‐controlled acute therapy period were randomly reassigned in a 2:1 ratio to therapy with duloxetine 60 mg BID (N = 197) or routine care (N = 96) for an additional 52 weeks. Patients.  The trial included outpatients ≥18 years of age diagnosed with moderate to severe DPNP caused by type 1 or type 2 diabetes. Results.  Fourteen patients discontinued due to adverse events or death (11 [5.6%] duloxetine‐ and 3 [3.1%] routine care‐treated patients). There were no significant therapy‐group differences observed for patients with ≥1 serious adverse event. In total, 110 (55.8%) duloxetine‐ and 47 (49%) routine care‐treated patients had ≥1 treatment‐emergent adverse event (TEAE). The TEAE with a significant therapy‐group difference, with patients in the duloxetine therapy group experiencing a higher percentage of events, was asthenia (11 [5.6%] duloxetine‐ vs no routine care‐treated patients). Duloxetine did not appear to adversely affect lipid profiles, or nerve or eye function. There were no significant therapy‐group differences observed in mean change in systolic blood pressure, weight, or electrocardiogram parameters. Significant therapy‐group differences were observed in favor of duloxetine in the SF‐36 physical component summary score, and subscale scores of physical functioning, bodily pain, mental health, and vitality. Conclusions.  The results of this study provide support for the use of duloxetine in the long‐term management of DPNP.